http://www.athensjournals.gr/education/2017-4-1-5-Zervas.pdf - Theodore G. Zervas (Athens Institute for Education and Research, 2017)
When looking at the historical past, questions of diversity and school reform seem to go hand in hand. The presence of diverse communities in American urban schools has helped foster a change in traditional educational practices and policies. At times, the goal for these communities was to be given their just share of receiving a fair, equitable, and democratic education. However, when evaluating America's historical timeline, issues of diversity in American urban schools emerge when major social and political events impact aspects of American social life. The period 1880-1900 saw vast numbers of immigrants, mostly from Europe, settling in America's metropolitan cities. Some of these immigrants had aspirations of beginning a new life in the United States, while others sought to work hard, make a bit of money and return back home with their newfound wealth. Those that did settle brought with them their customs and traditions, languages and religions as well as their unique views on education. This essay explores how several immigrant groups in the United States reacted to the already present modes of schooling, and how American schools responded to the educational needs and educational demands of these groups.